The Interference of Communication Patterns in Diplomatic Discourse - GHAZARYAN, GRIGOR (Bulletin of Yerevan University B: Philology, 2021)
The paper deals with the problem of interference of communication patterns in the textual model of diplomatic communication based on the analyses of verbal notes in different languages. As a basic format of written communication between a foreign ministry and an embassy accredited in a state, notes verbales have certain stable structural characteristics. It is noted that in those types of notes, certain patterns are the same across different languages. Diplomatic correspondence presents anexample of semi-structured information which is endowed with high potential of generating transfers in its oral and interference in its written forms.The contrastive analysis of the notes demonstrated that certain patterns, being recurrent in texts of the same format in different languages, appear as stable structured elements. Besides, diplomatic texts with all their aspects of hypertextuality and intertextuality can become the material of future research aimed at identifying language distance.
Keywords: note verbale, diplomatic language, interference, transfer, borrowing, translation